City Development Strategy South Asia Region : Progress Report - World Bank (Washington, DC, 2014)
This report highlights the discussion, processes, lessons learned in examining innovative options for participation by all stakeholders in seeking new social and economic contracts between civil society and urban governments. The improvement in relationships is geared towards providing better services for urban poor and directly contributing to urban poverty alleviation. The report attempts to capture the new wave of enthusiasm and entrepreneurial inclination to city management that is more transparent and responsive to citizens as 'customers'.